1995
DOI: 10.1136/ard.54.11.867
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and bone turnover in spinal osteoarthrosis.

Abstract: Objectives-To determine whether there was a generalised increase in bone mineral density (BMD) in spinal osteoarthrosis (OA), and to determine the mechanism of this possible protection against osteoporosis as assessed by biochemical markers ofbone turnover. Methods-We studied 375 women (ages 50 to 85) from a population based group. Spinal OA was defined from radiographs as the presence of degenerative changes affecting intervertebral or facet joints. BMD of the lumbar spine (LS), femoral neck (FN) and total bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 16 publications
4
41
2
2
Order By: Relevance
“…The findings showed the global skeletal involvement in OA, being the changes present not only at the affected joints but also in other articular areas. More recent studies have confirmed these findings [20][21][22].…”
Section: Discussionmentioning
confidence: 58%
“…The findings showed the global skeletal involvement in OA, being the changes present not only at the affected joints but also in other articular areas. More recent studies have confirmed these findings [20][21][22].…”
Section: Discussionmentioning
confidence: 58%
“…The hip and knee joints have been most studied, with several groups finding evidence of higher systemic BMD in those with OA at these joint sites in a variety of populations. [7][8][9][10][11] Higher BMD has also been reported in association with OA of the spine 10,12 and hand. 9,10,13 A limitation of cross-sectional studies is that the direction of causality cannot be formally assessed.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 99%
“…Cross-sectional investigations into the relationship between OA and bone turnover, which is generally inversely related to BMD owing to its role in bone loss, 33 have yielded conflicting findings. Levels of serum or urine bone turnover markers have been reported as both increased 34 and decreased 12,16 in individuals with radiographic OA of different joints compared with controls, with other studies reporting no association between bone turnover markers and radiographic OA severity. 35 Conversely, prospective studies suggest that higher rates of bone turnover may be related to more rapid OA progression.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 99%
“…Ultrasound techniques are radiation-free, easy-tooperate, inexpensive and rapid, and they offer a reasonable alternative for the initial evaluation of elderly patients with osteoporosis [13]. Since several studies have reported finding a direct association between high BMD and osteoarthritis in the lumbar spine [7,15,16,27], we carried out this study to find out whether QUS might be useful in predicting the extent of degenerative changes in the lumbar spine of subjects experiencing pain. Our results showed a significant direct correlation between lumbar spinal stenosis and QUS parameters.…”
Section: Discussionmentioning
confidence: 99%